Analisis Kinerja Keuangan PT Telekomunikasi Indonesia TBk Periode 2018-2020 - Budi Dharma; Rio Ariangga; Muhammad Anshari (Universitas Muhammadiyah Enrekang, 2022)
Based on three factors, namely profitability, solvency and liquidity ratios, this study aims to assess the financial performance of PT.Telekomunikasi Indonesia, Tbk (PT. Telkom). The main subject of this research is the Indonesian Telecommunications Company. This study seeks to explain financial performance based on the ratios of liquidity, solvency and financial profitability examined by Telkom. This study adopts a quantitative strategy and uses a descriptive method. Financial ratios are used to assess the financial health of an organization. The three financial ratios used are liquidity, solvency and profitability. These results show the liquidity ratio at PT. Telekomunikasi Indonesia, Tbk is not in a good position from 2018 to 2020 based on quick ratio and current ratio. In PT, solvency ratio. However, in terms of debt to asset ratio, Indonesian telecommunications are not in good condition based on the analysis of the debt to equity ratio. PT. Telekomunikasi Indonesia, Tbk. have examined the return on equity and return on investment. PT's financial performance will be determined by this research. Telkom's profitability, liquidity and solvency ratios. This research has PT. Telkom as the main subject. PT. Telkom's financial performance is the subject of this research. Liquidity ratios, solvency and financial profitability are examined by Telkom. Quantitative and descriptive methods are used in this study. The company's financial performance is evaluated by using financial ratios. The financial metrics used are liquidity, solvency and profitability ratios. These results show the liquidity ratio at PT. Telekomunikasi Indonesia, Tbk is not in a good position for 2018 to 2020 both in terms of current ratio and fast ratio. solvency ratio to PT. Debt-to-equity ratio analysis shows that Indonesian telecommunications are not in good condition, however, the debt-to-asset ratio contradicts this. PT. Telekomunikasi Indonesia, Tbk. have examined return on equity and investment from both angles.